Abstraction and meaning in the animation of Hong Kong artists. Issue 1 (1st December 2020) - Hattler, Max
This article discusses the experimental animation works of Choi Sai-Ho, Carla Chan, Tobias Gremmler and Chris Cheung Hon-Him to probe animated abstraction as a discursive space through which meaning can be negotiated. These Hong Kong artists explore alternative, open-ended and fluid ways of meaning-making that are emerging in response to more traditional modes of moving image storytelling. In developing a narrative-abstraction vocabulary for artists and scholars to work with, what role can the works of Hong Kong artists play in shaping this, and what perspectives can these works offer for such an endeavour? A range of preoccupations with references ranging from spiritual symbolism and abstracted landscape to Chinese opera and Hong Kong architecture bring to light some of those other visions and possible modes of animated abstraction engaged with producing meaning.